2008
DOI: 10.1016/j.envres.2008.07.003
|View full text |Cite
|
Sign up to set email alerts
|

Biomarkers of kidney integrity in children and adolescents with dental amalgam mercury exposure: Findings from the Casa Pia children's amalgam trial

Abstract: Mercury is toxic to the kidney, and dental amalgam is a source of mercury exposure. Few studies have evaluated the effects of dental amalgam on kidney function in a longitudinal context in children. Here, we evaluated urinary concentrations of glutathione S-transferases (GSTs) α and π as biomarkers of renal proximal and distal tubular integrity, respectively, and albumin as a biomarker of glomerular integrity in children and adolescents 8-18 years of age over a 7 year course of dental amalgam treatment. Five h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 33 publications
0
20
0
2
Order By: Relevance
“…This study adds to the growing body of literature affirming the safety of amalgam as restorative material. [13][14][15][16][17] When the additional factor of the greater longevity of amalgam was compared with composite, 8,18,19 the continued viability of amalgam as a restorative material is confirmed.…”
Section: Commentary and Analysismentioning
confidence: 81%
“…This study adds to the growing body of literature affirming the safety of amalgam as restorative material. [13][14][15][16][17] When the additional factor of the greater longevity of amalgam was compared with composite, 8,18,19 the continued viability of amalgam as a restorative material is confirmed.…”
Section: Commentary and Analysismentioning
confidence: 81%
“…These publications were translated by Russian or Chinese speakers before inclusion. Some publications were considered together (Bellinger et al, 2006; Geier et al, 2013; Hawkesworth et al, 2013; Barregard et al, 2008; DeRouen et al, 2006; Skroder et al, 2015; Woods et al, 2008; Kooijman et al, 2015; Taal et al, 2011), as they used the same study population and provided complementary information. Most studies were from non-occupationally-exposed populations, one included children of occupationally exposed parents (Khan et al, 2010).…”
Section: Resultsmentioning
confidence: 99%
“…manganese (Nascimento et al, 2016), mercury (Barregard et al, 2008; de Burbure et al, 2006; Woods et al, 2008; Geier et al, 2013; Bellinger et al, 2006; DeRouen et al, 2006), selenium (Skroder et al, 2015), thallium (Weaver et al, 2014), or uranium (Weaver et al, 2014) (Table 2). These studies covered Egypt, France, Poland, Czech Republic, Portugal, China, Bangladesh, Mexico, Thailand, Brazil, and the United States.…”
Section: Resultsmentioning
confidence: 99%
“…10,11 Investigators examined both GST-a and -p in children with and without amalgams (amalgams versus resin composites) over an 8-year-period as a part of the Casa Pia children's amalgam trial (the parent study). 7 The parent study showed no significant difference between the two groups on GST-a and -p levels; however, the dose-dependent relationship between cumulative Hg and GST-a and -p levels was not examined.…”
Section: Introductionmentioning
confidence: 94%